Relationship between Occupational Prestige and Working Hours - Spoorthi GVN (International Journal of Advanced Science and Technology, 2020)
Status has always been overemphasized through work and performance. This paper is about the occupational prestige judgment made by people with regard to the dedication and commitment they give for their work. the prestige of an individual is based on material matters such as income, education, training, experience. Working for extended hours in nowadays work culture seems to be an added factor to how everyone views the status of the prestige of a person. The study used regression analysis to test two factors that determine the relationship and the findings suggest there is a relationship between occupational prestige and the number of working hours but there seems to be a weak relationship.